2017
DOI: 10.1038/onc.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant low expression of p85α in stromal fibroblasts promotes breast cancer cell metastasis through exosome-mediated paracrine Wnt10b

Abstract: P85α, which acts as a tumour suppressor, is frequently found to be downregulated in various human cancers. However, the role of p85α in the tumour microenvironment is unknown. Here, we report that aberrantly low expression of p85α in breast cancer stroma is clinically relevant to breast cancer disease progression. Stromal fibroblasts can acquire the hallmarks of cancer-associated fibroblasts (CAFs) as a result of the loss of p85α expression. Paracrine Wnt10b from p85α-deficient fibroblasts can promote cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 58 publications
(63 reference statements)
1
93
0
Order By: Relevance
“…Wnt ligands (Wnt10b/3) or receptors (FZD7/LRP6) mediate activation of the β-catenin pathway responsible for EMT induction. 29,[57][58][59][60] In contrast, Wnt5a/5b-induced EMT is not dependent on β-catenin, but is involved in FZD2/STAT3 signaling. 61 Ectopic expression of DKK1/SFRP1 or recombinant DKK1/SFRP1 suppresses breast epithelial cell EMT, further proving the role of Wnt ligands and receptors in this process.…”
Section: Cancer Cell Epith Elial-mesenchymal Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wnt ligands (Wnt10b/3) or receptors (FZD7/LRP6) mediate activation of the β-catenin pathway responsible for EMT induction. 29,[57][58][59][60] In contrast, Wnt5a/5b-induced EMT is not dependent on β-catenin, but is involved in FZD2/STAT3 signaling. 61 Ectopic expression of DKK1/SFRP1 or recombinant DKK1/SFRP1 suppresses breast epithelial cell EMT, further proving the role of Wnt ligands and receptors in this process.…”
Section: Cancer Cell Epith Elial-mesenchymal Transitionmentioning
confidence: 99%
“…Both canonical and noncanonical Wnt pathways are involved in EMT of breast stem cells or cancer cells. Wnt ligands (Wnt10b/3) or receptors (FZD7/LRP6) mediate activation of the β‐catenin pathway responsible for EMT induction . In contrast, Wnt5a/5b‐induced EMT is not dependent on β‐catenin, but is involved in FZD2/STAT3 signaling .…”
Section: Wnt Signaling Induces Breast Cancer Cell Epithelial‐mesenchymentioning
confidence: 99%
See 1 more Smart Citation
“…These cell contents, when transferred to recipient cells, can alter its biologic behavior, including intracellular signaling pathways 10 . Exosomal contents, therefore, have the ability to act as either tumor suppressors or promoters through their direct actions on a cell or by modifying the microenvironment 13, 14, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that CAFs secret CD9+ exosomes to directly stimulate the migration ability of scirrhous‐type gastric cancer cells; they also deliver exosomal miR‐451 as a signaling molecule to provide a favorable niche for esophageal tumor cells migration and cancer progression. In breast cancer, stromal fibroblasts can acquire the hallmarks of CAFs as a result of the loss of p85α expression; subsequently, these p85α low‐expressed CAFs would transport exosomes containing Wnt10b to promote cancer metastasis via canonical Wnt pathway mediated EMT process . Additionally, in breast cancer, miR‐21 and two other miRNAs, 378e and 143, are increased in exosomes released from CAFs, promoting the aggressive nature of cancer cells, increasing stem cell amounts, and inducing EMT …”
Section: Exosomes In Sequential Processes Of Tumor Metastasismentioning
confidence: 99%